Pemaknaan Qalb Salīm dengan Metode Analisis Semantik Toshihiko Izutsu - Lukita Fahriana (Refleksi: Jurnal Kajian Agama dan Filsafat, 2019)
The word Qalb Salīm contained in the Qur’an, often interpreted with the meaning of “a clean heart” by the commentators of the Qur’an. In fact, to express the meaning of a clean heart, the Qur’an has the equivalent own word that is “wa liyumaḥḥiṣa mā fī qulūbikum”. It makes the meaning of “a clean heart” is less appropriate to be used as the meaning of Qalb Salīm. Thus, in this paper will be carried out re-interpretation of the word Qalb Salīm with the use of semantic Toshihiko Izutsu. Through the semantic Toshihiko Izutsu, will be known about basic meaning of Qalb Salīm, relational meaning of Qalb Salīm, and changes meaning of Qalb Salīm that occurs from period to period (pre-Qur’anic, Qur’anik, and post-Qur’anik). In addition, it will be known also about the world view of the meaning of the word Qalb Salīm. So, it will be generated meaning of Qalb Salīm not only textually, but also contextually.